Aporphine alkaloids with in vitro antiplasmodial activity from the leaves of Phoebe tavoyana - Omar H.; Fadaeinasab M.; Taha H.; Widyawaruyanti A.; Nafiah M.A.; Rachmatiah T. (Taylor and Francis Ltd., 2023)
antimalarial agent; aporphine derivative; boldine; chloroquine; laetanine; laurolitsine; roemerine; sebiferine; tavoyanine A; unclassified drug; alkaloid; antimalarial agent; aporphine derivative; plant extract; antiplasmodial activity; Article; carbon nuclear magnetic resonance; controlled study; drug isolation; electrospray mass spectrometry; heteronuclear multiple bond correlation; heteronuclear multiple quantum coherence; in vitro study; Lauraceae; nonhuman; Phoebe tavoyana; plant leaf; Plasmodium falciparum; proton nuclear magnetic resonance; chemical structure; Alkaloids; Antimalarials; Aporphines; Lauraceae; Molecular Structure; Plant Extracts; Plant Leaves; Plasmodium falciparum